Employees' perception of fairness and satisfaction of performance appraisal at Sabah Forestry Development Authority (SAFODA) / Fiona Evelyn Anthony - Anthony, Fiona Evelyn (2016)
This study, undertaken at the Sabah Forestry Development Authority (SAFODA) is entitled "Employees' Perception of Fairness and Satisfaction of Performance Appraisal at Sabah Forestry Development Authority (SAFODA)." The main objective of this study is to examine the perception of fairness, and the level of satisfaction of employees with the current performance appraisal practice at the organisation, and present the findings and recommendations to the management of SAFODA for further reference and consideration. A survey was conducted on a sample of 80 employees at SAFODA, but only 55 surveys were managed to be collected. Data analysis using SPSS version 21 and several tests were conducted using independent t-test, ANOVA and Pearson's correlation test to arrive at the desired results. Findings from this study revealed that respondents perceived the performance appraisal practice in SAFODA as fair, and the positive correlation between perception of fairness with distributive justice, procedural justice and informational justice with reaction towards Performance Planning and Review (PPR) and also significant correlation between interpersonal justice and reaction towards Performance Planning and Review (PPR) indicated respondents satisfaction with the performance appraisal practice in SAFODA. Organisational justice dimensions of distributive justice, procedural justice, informational justice and interpersonal justice have a strong correlation with satisfaction toward the supervisor. Overall, employees perceived the performance appraisal practice as fair, and were generally satisfied with it. It is suggested that the management of SAFODA use a different method of appraising employees' performance apart from the established and current practice used in the civil service. Peer evaluation is recommended as it is a unique method of evaluation, which gives wider picture of individual employees' actual performance and provide better perspective in term of reducing the possibility of injustice outcomes of employees' performance appraisal.